A Neo-Schumpeterian approach towards public sector economics - Horst Hanusch; Andreas Pyka; Florian Wackermann (Universität Augsburg, Institut für Volkswirtschaftslehre, 2009)
Innovation is the major driver of economic growth and development. To analyze innovation processes the restriction of a framework suited to the analysis of innovation towards the industrial sphere of an economy is not sufficient because of the important co-evolutionary dimensions of innovation. Instead, a comprehensive economic theoretical approach is needed which encompasses all spheres of economic life. This paper is filling this gap by introducing Comprehensive Neo-Schumpeterian Economics and the Neo-Schumpeterian approach towards public sector economics.
urn:nbn:de:bvb:384-opus4-711233
Keywords: B52; H11; L2; O20; P0; 330; Innovation; uncertainty; public sector; co-evolution; Öffentlicher Sektor; Innovation; Evolutionsökonomik; Schumpeterismus; Theorie